The Effect of Hormone Replacement Therapy on Dry Eye Syndrome Evaluated with Schirmer Test and Break-Up Time - Yanhong Feng; Gang Feng; Shuli Peng; Hui Li (Journal of Ophthalmology)
Hormone replacement therapy (HRT) for dry eye syndrome (DES) is controversial in clinical practice. The goal of this study was to review relevant studies and analyze the pooled data to determine whether HRT is effective for DES. In this study, a literature search of PubMed, Embase, and Cochrane databases up to May 2015 was performed, with the search restricted to English language publications. The studies were screened after reading the abstract and full text. Only studies related to the effect of HRT on DES were included in the meta-analysis. Results of Schirmer tests with and without anesthetics and tear break-up time (BUT) values data were extracted and entered into RevMan software to meta-analyze the overall effect of HRT on DES. A total of 43 studies were identified, and 21 of these studies were found to be related to the effect of HRT on DES. Ultimately, 5 studies were included in the final meta-analysis. The pooled results revealed that HRT can affect Schirmer test results without anesthetics but does not affect Schirmer test results with anesthetics and BUT. The results indicate that HRT might improve DES symptoms when measuring basal tear production without anesthesia.